ORGANIZATION CHALLENGES AND SOLUTIONS OF THE STATE HEALTH INSURANCE SYSTEM IN UZBEKISTAN (Eureka Journal of Health Sciences & Medical Innovation, 2026)
The effective mechanisms for organizing the state health insurance system (SHIS) in Uzbekistan play a crucial role in ensuring equitable and sustainable access to healthcare services. This article analyzes the challenges and potential solutions for implementing SHIS in Uzbekistan, based on the review of 15 scientific sources published over the last five years. The analysis focuses on key factors such as financing sustainability, social protection, the composition of insurance packages, service delivery efficiency, and digital infrastructure. Furthermore, international experiences, particularly from Germany, South Korea, and European countries, are adapted to the Uzbek context to provide recommendations. The findings of this study provide a scientific foundation for evidence-based policy-making to improve the state health insurance system in Uzbekistan.
Keywords: state health insurance, financing, insurance packages, social protection, Uzbekistan, service delivery efficiency, digital health